Report of the Group of Officials on Centrally Sponsored Schemes - Planning Commission (Planning Commission, 1987)
Until the Fourth Five Year Plan, Central assistance to States for implementation of Plan programmes within, the States jurisdiction was given in the form of scheme-wise allocation of funds. This resulted in rigidities and inefficiencies in the system and inequitable distribution of Central assistance. The matter was raised in several meetings of NDC. on the basis of discussions in NDC, the concept of block assistance for State Plans was subsequently introduced.
Planning Commission
Planning Commission